Infections and systemic vasculitis - B. S. Belov; O. N. Egorova; G. M. Tarasova; N. V. Muravieva (Современная ревматология, 2022)
Infections and systemic vasculitis (SV) are characterized by mutual influence, which increases the risk of occurrence, aggravates the course and outcome of the disease. The review considers the issues related to both the trigger role of infections in the development of SV and comorbid infections (CI) that complicate the course of the disease. Recognition of the infectious etiology of SV is of great importance, since it requires a comprehensive examination and, if necessary, early and complete etiotropic treatment. Since SV per se and the use of both induction and maintenance immunosuppressive therapy are significant risk factors for secondary CIs, special attention should be paid to the prevention of the latter, including vaccination, primarily against influenza and pneumococcal infections.